Translational control in cortical development - Federico Cremisi; Robert Vignali (Frontiers Media S.A., 2023)
Differentiation of specific neuronal types in the nervous system is worked out through a complex series of gene regulation events. Within the mammalian neocortex, the appropriate expression of key transcription factors allocates neurons to different cortical layers according to an inside-out model and endows them with specific properties. Precise timing is required to ensure the proper sequential appearance of key transcription factors that dictate the identity of neurons within the different cortical layers. Recent evidence suggests that aspects of this time-controlled regulation of gene products rely on post-transcriptional control, and point at micro-RNAs (miRs) and RNA-binding proteins as important players in cortical development. Being able to simultaneously target many different mRNAs, these players may be involved in controlling the global expression of gene products in progenitors and post-mitotic cells, in a gene expression framework where parallel to transcriptional gene regulation, a further level of control is provided to refine and coordinate the appearance of the final protein products. miRs and RNA-binding proteins (RBPs), by delaying protein appearance, may play heterochronic effects that have recently been shown to be relevant for the full differentiation of cortical neurons and for their projection abilities. Such heterochronies may be the base for evolutionary novelties that have enriched the spectrum of cortical cell types within the mammalian clade.